Faktor-Faktor yang Mempengaruhi Pendapatan Masyarakat di Sekitar Kawasan Kurma Indonesia - Hasan Basri; Nurdin Nurdin; Ali Fahmi; Albetris Albetris (Ekonomis: Journal of Economics and Business, 2022)
This study aims to: 1) find out and analyze how the effect of the number of family members partially on people's income; and 2) knowing and analyzing how the influence of education level partially on people's income. The results of this study reveal that 1) partially family member variables have no effect on the income level of the community around the Kurma Jambi area; and 2) partially the education level variable has a significant and positive effect on the income of the community around the Jambi date palm area.